Do persons with intellectual disability have a social life?The Israeli reality ¿Tienen las personas con discapacidad intelectual vida social?La realidad Israelí - Ilana Duvdevany (Instituto Nacional de Salud Pública, 2008)
Living in the community does not, in and of itself, guarantee social integration and inclusion for persons with intellectual disability. Social life and leisure participation can indicate the beginning of such a process and its impact on the quality of life. The present study investigated the social life quality of persons with intellectual disability who live in community settings or with foster families and its impact on their quality of life. The sample consisted of 85 adults with intellectual disability, ranging in age from 18 to 55 years. Forty-five of them lived in community residential settings and 40 lived with foster families in Israel. Five questionnaires were used: 1) a demographic questionnaire; 2) Quality of Life Questionnaire;¹ 3) the Revised UCLA Loneliness Scale;² 4) Social Relationships List;³ and 5) Leisure Activities List.³ The main findings showed no significant differences between the two groups in social life or feelings of loneliness. Foster residents were more involved and more independent in their leisure activities than were those who lived in community residences. An association between social life and quality of life was partly confirmed. The need for intervention programs and leisure education programs is discussed. El hecho de vivir en una comunidad no garantiza, por sí mismo, ni la integración ni la inclusión de los discapacitados intelectuales. Las amistades y la participación en actividades recreativas pueden ser indicadores de que tal proceso comienza a darse y de su impacto en la calidad de vida. El presente trabajo investigó la calidad de vida social de personas con discapacidad intelectual que viven en residencias comunitarias y con familias adoptivas y su impacto en cuanto a calidad de vida. La muestra consistió de 85 adultos con discapacidad intelectual de edad entre 18 y 55 años. Cuarenta y cinco de ellos viven en áreas comunitarias residenciales y 40 con familias adoptivas en Israel. Se utilizaron cinco cuestionarios: 1) un cuestionario demográfico; 2) el Cuestionario de Calidad de Vida;¹ 3) la Escala de Soledad Revisada de la UCLA;² 4) el Catálogo de Relaciones Sociales;³ y 5) el Catálogo de Actividades Recreativas.³ En general no se encontraron diferencias significativas entre los dos grupos en lo referente al número de amistades o en cuanto a los sentimientos de soledad. Los residentes con familias adoptivas tendieron a involucrarse más y a ser más independientes en sus actividades recreativas que los que vivían en residencias comunitarias. Se confirmó en parte una relación entre vida social y calidad de vida. Se discute la necesidad de programas de intervención y educación de la recreación.